Pelvic Abscess Caused by Ureteral Calculus and Abscess Treatment through Aspiration by Transperineal Puncture - Bo-Ran An; Chao Gao; Di An (Case Reports in Urology)
Pelvic abscess is mostly caused by gynecological inflammation or digestive system diseases such as appendicitis or Crohn’s disease. This case of pelvic abscess originates from ureteral calculus and is not commonly seen in clinical practice. This is mainly due to the patient’s ureteral stones not being actively treated. After local puncture and pus extraction, as well as the application of effective antibiotics, the patient recovered. Therefore, this case provides clinical doctors with experience that ureteral stones may cause serious complications and should be actively treated after detection.